PEMANFATAAN APLIKASI E-SAWIT KITA SEBAGAI MEDIA PEMBELAJARAN SERTA MENCIPTAKAN INFORMASI AKTUAL DAN KOLABORASI ANTAR PETANI SAWIT - Andesti, Cyntia Lasmi; Amuharnis, Amuharnis; Sirait, Weri; Nurhidayat, Nurhidayat; Lonanda, Fitria; Karfindo, Karfindo; Dian, Rahmad (Jurnal Pengabdian Masyarakat Nasional, 2024)
The use of information technology in the agricultural sector is increasingly important to increase productivity and collaboration between farmers. This training explores the use of the E-Sawit Kita application as a learning medium and means of creating actual information for palm oil farmers. This training provides educational material related to best cultivation practices, land management and relevant market information. In addition, this research also involves intensive training for farmers in using the application, with the aim of increasing their understanding and skills in utilizing this technology. With interactive features, E-Sawit Kita allows farmers to share experiences, challenges and solutions, which in turn strengthens the collaborative network between them. The method used in this training is in the form of lectures, training material and questions and answers about using the E-Sawit Kita application. The research results show that E-Sawit Kita, through the training it provides, not only increases farmers' knowledge and skills, but also strengthens community solidarity through continuous exchange of information. These findings provide valuable insights for the development of similar applications to support sustainable agriculture in Indonesia.